PENGARUH KONTEN MEDIA SOSIAL TERHADAP POLA KONSUMSI BERITA - Marleen Muskita; Bernadine Putri Andris (JURNAL BADATI, 2024)
The development of communication and information technology which gave birth to the internet as an electroniccommunication network, digital technology developments and technology, mobile. In addition to democratic social order becoming a world ideology, it has encouraged various countries to eliminate barriers in the production anddistribution of information. Like media consumption, this news consumption pattern can be operationalized into the amount of time spent on various types of media, the media content consumed, and the various relationships betweenindividual consumers. media with the content of the media consumed or the media as a whole (Rosengren in Rakhmat, 2001, p. 66). Understanding an audience's media consumption patterns also indirectly provides input on the use of the types of mass media that are most trusted and considered credible by the audience. Results of hypothesis testing ofsocial media content on news consumption patterns. From the results of the t test, it can be seen that tcount is 3.441 with a significance level (?) = 0.05, namely 1.701 because tcount is 3.441 ttable 1.701, meaning that social media content has a positive influence on news consumption patterns. Based on the calculation results, it explains themagnitude of the coefficient of determination or R Square of 0.297 (0.297 × 100%), this shows that the percentage contribution of the influence of the independent variable social media content on the dependent variable news consumption patterns is 29.7% or the independent variable used in the model is able to explain the variance the newsconsumption pattern variable was 29.7%, while the remaining 70.3% (100%-29.7%) was influenced by other variables not included in the research model.